1994
DOI: 10.1007/bf02300387
|View full text |Cite
|
Sign up to set email alerts
|

Role of electrogastrography and gastric impedance measurements in evaluation of gastric emptying and motility

Abstract: Electrogastrography records electrical potential variations brought about by myoelectrical activity of the stomach. Abnormal myoelectrical rhythms such as tachygastrias may also be detected. Electrogastrography provides little information on gastric motility and emptying. Impedance epigastrography is a technique that uses changes in epigastric impedance to evaluate gastric emptying of large-volume liquid meals. The results are inferior to those of tomographic impedance imaging. Phasic antral contractions may l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…For example, some clinicians, utilizing electrogastrography (EGG) to evaluate symptoms of dyspepsia, gastroparesis or other motility disorders, attempt to determine whether slow wave frequency conforms to accepted ‘normal’ limits of 2–4 cpm (Koch, 2001; Lin & Chen, 2001; Leung et al 2006; Sha et al 2009). However, the correlation between symptoms and slow wave frequency, as assessed by EGG, is not strong (Jebbink et al 1994; Smout et al 1994; Chen et al 1996; Parkman et al 1997), and reasons for this need to be clarified.…”
Section: Introductionmentioning
confidence: 98%
“…For example, some clinicians, utilizing electrogastrography (EGG) to evaluate symptoms of dyspepsia, gastroparesis or other motility disorders, attempt to determine whether slow wave frequency conforms to accepted ‘normal’ limits of 2–4 cpm (Koch, 2001; Lin & Chen, 2001; Leung et al 2006; Sha et al 2009). However, the correlation between symptoms and slow wave frequency, as assessed by EGG, is not strong (Jebbink et al 1994; Smout et al 1994; Chen et al 1996; Parkman et al 1997), and reasons for this need to be clarified.…”
Section: Introductionmentioning
confidence: 98%
“…At the time being, however, the sonographic techniques as well as more sophisticated techniques such as electrical impedance epigastrography (35), electrical impedance tomography (36,37), high speed impedance tomography (38), magnetic resonance imaging (39) and echoplanar magnetic resonance imaging (40) may be useful in the research setting but cannot be recommended as tools to record gastric emptying in clinical practice.…”
mentioning
confidence: 99%
“…It has been suggested that these waves could be reflections of gastric contractions, 5 but simultaneous antroduodenal manometry failed to show an association between IGG and antral contractile activity in the fasting state. 21 A simultaneous relation between the IGG and the electrical activity from the stomach measured with electrogastrography (EGG) 2 was, however, supporting the assumption that the waves were of gastric origin. A small variation in the intrinsic frequency of the gastric pacemaker with a temporarily decreased postprandial frequency followed by an increase have been shown employing both IGG and EGG.…”
Section: Discussionmentioning
confidence: 97%